LEGO Minecraft games book - March, Julia; Hugo, Simon (DK/Penguin Random House, 2025)
Build in some time for bite-sized family fun with the LEGO Minecraft Games Book, packed with hours' worth of ideas for LEGO Minecraft games, puzzles, and challenges.